‘Candidatus Mycoplasma haematohydrochoerus’, a novel hemoplasma species in capybaras (Hydrochoerus hydrochaeris) from Brazil - Vieira, Rafael F.C.; Santos, Nelson J.R.; Valente, Jessica D.M.; Santos, Leonardo P.; Lange, Rogério R.; Duque, Juan C.M.; Ferrari, Marcos V.; Barros Filho, Ivan R.; Collere, Flávia C.M.; Ferrari, Larissa D.R.; Gonçalves, Luiz R. [UNESP]; Sanches, Gustavo S.; et al. (Elsevier, 2021)
Three different species of hemoplasmas have been described in rodents, Mycoplasma coccoides, ‘Candidatus Mycoplasma haemomuris’ and ‘Candidatus Mycoplasma haemosphiggurus’. Additionally, potentially novel hemoplasma species have been detected in wild rodents from Brazil, including capybaras (Hydrochoerus hydrochaeris). Capybaras are the largest rodent in the world and are well adapted to live within close proximity to humans, which increases the risk to spread of zoonotic pathogens. Herein, we investigate the occurrence and genetic diversity of hemoplasmas infecting free-ranging capybaras from southern Brazil. Blood samples and ticks from 17 capybaras were collected. Packed cell volume and total plasma protein were measured, DNA was extracted, and further screened by species-specific and pan-hemoplasma PCR assays targeting the 16S rRNA gene of hemoplasmas. Sixteen out of 17 (94.12%; 95% CI: 73.02–98.95%) were anemic. Only one young female was hypoproteinemic. All capybaras were infested by adults and nymphs of Amblyomma dubitatum ticks. Using the PCR assay targeting the 16S rRNA gene of M. coccoides, 13/17 (76.47%; 95% CI: 52.74–90.44%) capybaras were positive for hemoplasmas. When DNA samples were tested by the pan-hemoplasma PCR, 16/17 (94.12%; 95% CI: 73.02–98.95%) animals were positive. One out of 11 (9.09%) adult ticks salivary glands tested positive for hemoplasma by the pan-hemoplasma PCR assay. Sequencing and phylogenetic analysis of the 16S and 23S rRNA gene fragments confirmed that animals were infected by a novel hemotropic Mycoplasma sp. previously reported in capybaras from Brazil. Additionally, sequencing and phylogenetic analysis of the 23S rRNA gene from three hemoplasma-positive capybaras samples from a previous study performed in midwestern Brazil also confirm our findings. Based on phylogenetic and Neighbor-Net network analysis of the 16S rRNA and 23S rRNA genes, the name ‘Candidatus Mycoplasma haematohydrochoerus’ is proposed for this novel organism.
Keywords: Amblyomma dubitatum; Hemotropic mycoplasmas; Wild rodents